Wooden Boats and Shipping Organizations in the Middle Reaches of the Yangtze River (1700-1850) - Chen, Yao (TSEG - The Low Countries Journal of Social and Economic History, 2024)
Between 1700 and 1850, there were an estimated 125,000 wooden boats in the middle reaches of the Yangtze River, with a load capacity of more than two million tons. The transport capacity and the wide distribution of these boats demonstrate that the relationship between multitiered markets was growing closer, and China’s national market was expanding more widely. In this period, direct supervision from government was so difficult to implement effectively that the task of ensuring the safety and order of water transportation fell to the commercial agencies, such as boat brokers 船行 and quay controllers 埠头. The wooden-boat shipping business in the middle Yangtze River during the Qing dynasty was not in a totally disordered state. The spontaneously formed boatmen gangs 船帮 and boatmen lineages 船民家族 played an active and influential role in a specific area of local river transportation in the middle Yangtze River, illustrating that local arbitration and mediation mechanisms were formed to deal with socioeconomic conflicts among shipowners, merchants, local communities, and local governments in the regional commercial transportation network. However, it was not until the end of the nineteenth century that a powerful shipping institution or merchant’s organization that could effectively regulate the water transportation emerged, nor were there socioeconomic mechanisms set up to deal with the many kinds of shipping disputes that existed in the reaches of the middle Yangtze.